Acceptance sampling schemes for two-parameter Lindley lifetime products under a truncated life test. Issue 3 (4th May 2021) - Wu, Chien-Wei; Shu, Ming-Hung; Wu, Nien-Yun
ABSTRACT: In this study, an acceptance sampling plan is developed for a truncated life test when the lifetime of a product follows a two-parameter Lindley distribution. The pairs of required minimum sample size for inspection and the threshold number of failures for lot acceptance are determined for assorted combinations of Lindley-distributed parameters with the enacted termination time of test and contracted quality-and-risk standard levels ratified from supplier and buyer. Several dimensionless scales converted from ratios of lifetime quantities are introduced to accommodate wide-ranging testing parameters for constructing comprehensive plans' criteria that are flexible access and easy setup in broad applications. Finally, a graphical user interface is built to facilitate the data input, plan selection, criteria computation, and decision-making.